Successful Public Policy Lessons from Australia and New Zealand - Luetjens, Joannah; Mintrom, Michael; `t Hart, Paul (ANU Press, 2019)
In Australia and New Zealand, many public projects, programs and services perform well. But these cases are consistently underexposed and understudied. We cannot properly 'see'-let alone recognise and explain-variations in government performance when media, political and academic discourses are saturated with accounts of their shortcomings and failures, but are next to silent on their achievements. Successful Public Policy: Lessons from Australia and New Zealand helps to turn that tide. It aims to reset the agenda for teaching, research and dialogue on public policy performance. This is done through a series of close-up, in-depth and carefully chosen case study accounts of the genesis and evolution of stand-out public policy achievements, across a range of sectors within Australia and New Zealand. Through these accounts, written by experts from both countries, we engage with the conceptual, methodological and theoretical challenges that have plagued extant research seeking to evaluate, explain and design successful public policy. Studies of public policy successes are rare-not just in Australia and New Zealand, but the world over. This book is embedded in a broader project exploring policy successes globally; its companion volume, Great Policy Successes (edited by Paul 't Hart and Mallory Compton), is published by Oxford University Press (2019).